Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{3^{10}.\left(-5\right)^{21}}{\left(-5\right)^{20}.3^{12}}\)= \(\frac{3^{10}.\left(-5\right)^{20}.\left(-5\right)}{\left(-5\right)^{20}.3^{10}.3^2}\)= \(\frac{\left(-5\right)}{3^2}\)= \(\frac{-5}{9}\)
\(\frac{3^{10}.\left(-5\right)^{21}}{\left(-5\right)^{20}.3^{12}}=\frac{3^{10}.\left(-5\right)^{20}.\left(-5\right)}{\left(-5\right)^{20}.3^{10}.3^2}=\frac{-5}{3^2}\)
CHÚC BẠN HỌC TỐT!!!!
a/ 7*25-49/7*24+21
=( 7*25 ) - ( 49/7 ) * ( 24+21)
= 175 - 7 * 45
= 175 - ( 7*45 )
=175 - 315
= -140
mk k bít đúng k
Ta có:\(\frac{3^{10}\cdot\left(-5\right)\cdot21}{\left(-5\right)^{20}\cdot3^{12}}\)
\(=\frac{3^{10}\cdot\left(-5\right)\cdot21}{\left(-5\right)^{19}\cdot\left(-5\right)\cdot3^{12}}\)
\(=\frac{3\cdot7}{\left(-5\right)^{19}\cdot3^2}\)
\(=\frac{7}{\left(-5\right)^{19}\cdot3}\)
\(\frac{3^{10}.\left(-5\right)^{21}}{\left(-5\right)^{20}.3^{12}}=\frac{3^{10}.\left(-5\right)^{20}.\left(-5\right)}{\left(-5\right)^{20}.3^{10}.3^2}=\frac{-5}{3^2}=\frac{-5}{9}\)
\(\dfrac{7}{30}=\dfrac{21}{90};\dfrac{4}{45}=\dfrac{8}{90}\)